2008
DOI: 10.1007/s00436-008-0904-9
|View full text |Cite
|
Sign up to set email alerts
|

Some characteristics of host–parasite relationship for Cryptocaryon irritans isolated from South China

Abstract: A survey on the host range for the parasitic ciliate Cryptocaryon irritans was carried out among the major maricultured fish species in the Huizhou region of Guangdong Province in South China, and some characteristics of its host-parasite relationship were described. The survey showed that all ten investigated species of fish (representing six different families) were infected with C. irritans with similar susceptibility. In chemoattraction assays, sera and mucus collected from investigated fish strongly attra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 33 publications
2
21
1
Order By: Relevance
“…The immunity was strengthened by subsequent infections, which was consistent with the results of Dan et al (2008). Among all of the fish species that have been experimentally infected with C. irritans Dan et al, 2008Dan et al, , 2013Luo et al, 2007Luo et al, , 2008, the highest documented SIT value by far is what we found in the pompano of group II. When challenged by a lethal dose of theronts, those fish were protected completely, whereas none of the fish in group I and the control survived.…”
Section: Controlsupporting
confidence: 92%
See 3 more Smart Citations
“…The immunity was strengthened by subsequent infections, which was consistent with the results of Dan et al (2008). Among all of the fish species that have been experimentally infected with C. irritans Dan et al, 2008Dan et al, , 2013Luo et al, 2007Luo et al, , 2008, the highest documented SIT value by far is what we found in the pompano of group II. When challenged by a lethal dose of theronts, those fish were protected completely, whereas none of the fish in group I and the control survived.…”
Section: Controlsupporting
confidence: 92%
“…34 kD soluble membrane proteins Luo et al, 2008). In this study, the SIT of group II was higher than that of both other groups.…”
Section: Controlmentioning
confidence: 47%
See 2 more Smart Citations
“…Additionally, it could be very ecologically interesting that we only detected C. irritans in seawater 1 m deep. C. irritans has been known to display positive phototaxis [21] and/or chemoattraction [22]. It may be that, in the natural environment, C. irritans theronts swim from the bottom to the surface after excystment and then infect the host fish.…”
Section: Discussionmentioning
confidence: 99%